AutoCAD 2010 Instructor (McGraw-Hill Graphics) - Leach James A. (Mc Graw-Hill, 2010)
AutoCAD 2010 Instructor includes instruction in all the new features of AutoCAD 2010, while maintaining the pedagogy and complete coverage that have always been a hallmark of the Leach text. The text is command-oriented so chapters are centered around groups of related commands.